(untitled) (Trabalho & Educação, 2016)
This article aims, within its limits, to contribute, in a Marxist perspective, for the theoretical and conceptual understanding of some categories that permeate feminist studies, such as: Sexual Division of Work, Gender, Gender Relations and Social Relations of Sex. Although, some of these categories may (and are in most studies) considered synonymous, they are polysemous terms highly permeated by ideology and can lead to serious conceptual errors. From numerous studies made by national and international authors, its expectative is to serve as a starting point for those interested in the subject that hopes to make an informed and safe theoretical choice for their studies. ___ Este artigo objetiva, em seus limites, contribuir, em uma perspectiva marxista, para o entendimento teórico- conceitual de algumas categorias que permeiam os estudos feministas, tais como: Divisão Sexual do Trabalho, Gênero, Relações de Gênero e Relações Sociais de Sexo. Embora, enquanto definição, algumas dessas categorias possam (e o são na maioria dos estudos) ser consideradas sinônimas, são termos altamente polissêmicos, eivados de ideologias e podem conduzir a equívocos conceituais graves. A partir de inúmeros estudos realizados por autores nacionais e internacionais, espera-se servir de ponto de partida para os interessados pela temática que almejam fazer uma escolha teórica consciente e segura para seus estudos.